Modulation of Ethylene and Ascorbic Acid on Reactive Oxygen Species Scavenging in Plant Salt Response - Wang, Juan; Huang, Rongfeng (Frontiers in Plant Science, 2019)
Salt stress causes retarded plant growth and reduced crop yield. A complicated regulation network to response to salt stress has been evolved in plants under high salinity conditions. Ethylene is one of the important phytohormones, playing a major role in salt stress response. Increasing studies demonstrate that ethylene modulates salt tolerance through reactive oxygen species (ROS) homeostasis. Ascorbic acid (AsA) is a non-enzymatic antioxidant, contributing to ROS-scavenging and salt tolerance. Here, we mainly focus on the advances in understanding the modulation of ethylene and AsA on ROS-scavenging under salinity stress. We also review the regulators involved in ethylene signaling pathway and AsA biosynthesis to respond salt stress. Moreover, AsA pool is affected by many environmental conditions, the potential role of ethylene in AsA production is also extensively discussed. Novel insights into the roles and mechanisms of ethylene in AsA-mediated ROS homeostasis will provide critical information for improving crop salt tolerance.